Perinatal factors in non‐disabled ELBW school children and later performance. Issue 1 (2nd December 2012) - Zanudin, Asfarina; Gray, Peter H; Burns, Yvonne; Danks, Marcella; Watter, Pauline; Poulsen, Leith
<x xml:space="preserve">Abstract</x> Aim To determine the association between perinatal events and subsequent motor performance, cardiorespiratory endurance and respiratory function in non‐disabled extremely low birthweight (ELBW) school children at 12 years of age. Methods Forty‐eight ELBW infants were included in this study. The Movement Assessment Battery for Children (MABC), VO2max score as a measure of cardiorespiratory endurance and respiratory function testing were performed and perinatal variables were extracted from the children's hospital files. Children with MABC score ≤ 15th centile were described as having suspect motor performance. Children were classified as being unfit with a VO2max > 1 standard deviation below the mean according to gender and age. Perinatal risk factors were explored as risk factors for motor outcome, cardiorespiratory endurance and respiratory function. Results MABC category was significantly related with gender (P = 0.005) and chronic neonatal lung disease (P = 0.013). Multiple regression analysis showed motor outcome at 12 years to be independently related to male gender (P = 0.03) and chronic neonatal lung disease (P = 0.045). Sixty‐five per cent of all the children were identified as unfit. Chronic neonatal lung disease was significantly related to cardiorespiratory endurance (P = 0.03) and predicted VO2max at 12 years (P = 0.05). No perinatal factors were significantly related to respiratory function variables. Conclusion Male gender and chronic neonatal lung disease were associated with later motor outcome of ELBW school children. It is suggested that objective and consistent follow‐up from childhood through preadolescence are important to address motor and fitness issues especially for male children born with ELBW.